O ornitorrinco de criminalização: A construção social moral do miliciano a partir dos personagens da ‘violência urbana’ do Rio de Janeiro - Alexandre Werneck (Dilemas: Revista de Estudos de Conflito e Controle Social, 2015)
O objetivo deste artigo é analisar o papel desempenhado pelo miliciano na mecânica de efetivação da “violência urbana” do Rio de Janeiro como representação social. Para tanto, foi feita uma observação dos procedimentos de interpretação desse personagem em dois corpora institucionais relacionados: o relatório e as notas das reuniões produzidos pela CPI das Milícias fluminense e o processo de produção da lei que criminaliza a formação desses grupos. O estudo mostra como a construção moral do miliciano depende da coordenação de três outras representações, características da “linguagem da violência urbana”: o traficante, o policial corrupto e o matador.   The aim of the article The Criminalization Platypus: The Social, Moral Construction of The Militia Member Based on Characters of Urban Violence in Rio de Janeiro is to analyse the role played by the militia member in the mechanics of effectuating Rio de Janeiro’s “urban violence” as social representation. To this end the procedures for interpreting such a character were observed in two institutionally related bodies: the report and minutes produced by the Parliamentary Enquiry (CPI) meetings into the Rio de Janeiro militias and the process of producing the law that criminalizes the formation of such groups. The study shows how the moral construction of the militia member depends on the coordination of three other representations, characteristics of the “language of urban violence”: the drug dealer, the corrupt police officer and the killer. Keywords: militia member, drug dealer, killer, orrupt police officer, actantial system